2004
DOI: 10.1097/00000542-200401000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Modeling of Morphine-6-glucuronide-induced Analgesia in Healthy Volunteers

Abstract: A cumulative dose of 0.3 mg/kg M6G, given over 1 h, produces long-term analgesia greater than that observed with placebo, with equal dynamics (potency and speed of onset-offset) in men and women. Possible causes for the great intersubject response variability, such as genetic polymorphism of the micro-opioid receptor and placebo-related phenomena, are discussed. The predictive pharmacokinetic-pharmacodynamic model was applied successfully and was used to estimate M6G analgesia after morphine in patients with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
92
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 0 publications
4
92
0
1
Order By: Relevance
“…Of the so far accumulated knowledge on the molecular mechanism underlying the functional consequences of the variant (10 -15), the presented results agree best with the consistent experimental and clinical observations that this variant mainly decreases the opioid effects and/or increases the opioid dosing requirements to achieve analgesia (1)(2)(3)(4)(5)(6)(7)(8)(9). The results are also in strong agreement with the fMRI observation that the genetic variant mainly affects the effects of opioid analgesics on the sensory component of pain (17), which is emphasized by the fact that the main molecular effect was presently found in the S II region.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Of the so far accumulated knowledge on the molecular mechanism underlying the functional consequences of the variant (10 -15), the presented results agree best with the consistent experimental and clinical observations that this variant mainly decreases the opioid effects and/or increases the opioid dosing requirements to achieve analgesia (1)(2)(3)(4)(5)(6)(7)(8)(9). The results are also in strong agreement with the fMRI observation that the genetic variant mainly affects the effects of opioid analgesics on the sensory component of pain (17), which is emphasized by the fact that the main molecular effect was presently found in the S II region.…”
Section: Discussionsupporting
confidence: 82%
“…The human -opioid receptor variant N40D coded by the single nucleotide polymorphism (SNP) 2 118AϾG of the -opioid receptor gene, OPRM1 (dbSNP rs1799971; allelic frequency 8.2-17%) has been found to be associated with diminished opioid effects in experimental (1)(2)(3)(4)(5) and clinical (6 -9) settings. However, in vitro experiments trying to elucidate the underlying molecular mechanisms provided inconsistent results, falling short to support the comparatively strong clinical evidence of decreased opioid effects in carriers of the variant 118G allele.…”
mentioning
confidence: 99%
“…The A118G polymorphism occurs with an allelic frequency ranging from 10 to 40% (Kim et al 2004;Lötsch and Geisslinger 2005;Szeto et al 2001; dependent on population studied). Several earlier clinical studies showed that the presence of A118G polymorphism is associated with opiate effectiveness observed in patients (Janicki et al 2006;Klepstad et al 2004;Lötsch and Geisslinger 2005;Romberg et al 2004Romberg et al , 2005Shi et al 2002;Skarke et al 2003) as well as susceptibility to drug addiction (Bond et al 1998;Szeto et al 2001). On the other hand, some studies also reported a lack of a correlation between the presence of the A118G SNP and drug addiction (Arias et al 2006;Franke et al 2001;Gelernter et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The SNP has been previously reported to decrease the clinical potency of alfentanil, 8 morphine 3,7 and M6G. [3][4][5][6] An altered responsiveness of the hypothalamic-pituitary-adrenal axis in 118G carriers 26,27 further supports a functional consequence of the 118A4G SNP and probably affects a greater range of other clinical opioid effects. Possible therapeutic consequences of the 118A4G SNP are still controversial.…”
Section: Discussionmentioning
confidence: 71%
“…Functional associations with opioid therapy have so far mainly focused on the 118A4G single nucleotide polymorphism (SNP) located in exon 1 of the gene. Morphine 3 and its active metabolite www.nature.com/tpj morphine-6-glucuronide (M6G) 3,4 constricted pupils with a decreased potency and produced smaller analgesic effects 5,6 in carriers of the mutated OPRM1 118G allele as compared to non-carriers. Patients carrying the mutated 118G allele required higher doses of morphine 7 or alfentanil for pain therapy.…”
Section: Introductionmentioning
confidence: 99%